Effect of biomineralization on recovery of microplastics from the sediments - Tee, Jia Yi (Nanyang Technological University, 2023)
Millions of tons of plastic are generated every year, highlighting the indispensable role plastic has come to play in our lives. However, plastic is not highly biodegradable, leading to its accumulation in various environments, including on land and in the sea. Plastics in the oceans may undergo biomineralization, potentially causing biomineralized plastic to sink. This can result in an imbalance between the plastic entering and that being retrieved from the ocean. This imbalance is of utmost importance as the accumulation of plastic in marine environments poses a significant threat to ecosystems, marine life, and human health. In this report, we explore the use of MICP to biomineralise plastics and employ density separation techniques to see the effect of biomineralization on recovery of microplastics from the sediments.